2023
DOI: 10.1038/s41698-023-00414-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of microsatellite stable early-onset colorectal cancer as predictors of prognosis and immunotherapeutic response

Can Lu,
Xiaopeng Zhang,
Josefine Schardey
et al.

Abstract: The incidence of early-onset colorectal cancer (EO-CRC, in patients younger than 50) is increasing worldwide. The specific gene signatures in EO-CRC patients are largely unknown. Since EO-CRC with microsatellite instability is frequently associated with Lynch syndrome, we aimed to comprehensively characterize the tumor microenvironment (TME) and gene expression profiles of EO-CRC with microsatellite stable (MSS-EO-CRC). Here, we demonstrated that MSS-EO-CRC has a similar pattern of tumor-infiltrating immune ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…Further, because large studies have demonstrated that the majority of yo CRC are sporadic and genomic and consensus molecular profiling of the two cohorts have revealed contrasting results. 6 , 7 , 8 , 9 , 10 , 11 the conclusions of our study strengthen the suggestion that external or environmental/lifestyle factors that perturb the gut microbial abundance and composition may be a major contributor to yo CRC development.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Further, because large studies have demonstrated that the majority of yo CRC are sporadic and genomic and consensus molecular profiling of the two cohorts have revealed contrasting results. 6 , 7 , 8 , 9 , 10 , 11 the conclusions of our study strengthen the suggestion that external or environmental/lifestyle factors that perturb the gut microbial abundance and composition may be a major contributor to yo CRC development.…”
Section: Discussionsupporting
confidence: 83%
“… 9 yo CRC patients have been found to share a similar distribution of consensus molecular subtypes (CMSs) with ao CRC, with CMS2 being the dominant subtype in both cohorts. 10 However, another study showed CMS1 was the most prevalent subtype in yo CRC, with comparable CMS2 composition to ao CRC. 11 On the other hand, epidemiological data clearly suggest that yo CRC incidence has increased across successive birth cohorts since 1960.…”
Section: Introductionmentioning
confidence: 98%
“… 30 However, there are few reports on the molecular mechanisms of metastasis in different tumor locations in EOCRC, and further exploration is needed. 29 , 31 Although studies have indicated differences in distant metastases in EOCRC based on the primary tumor location, the reasons for these differences are still unclear. In addition to the primary tumor location, other factors such as demographic factors and clinical pathological factors also show significant differences in the occurrence and development of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While mutational comparisons between young and old CRC patients have been performed previously (11,12), only very recent studies have examined the transcriptional profiles of EOCRC compared with LOCRC (13)(14)(15)(16). These studies identified a variety of differences between EOCRC and LOCRC, including differences in immune signature (14,15) and predicted immunotherapy response (13). Other studies have found no such differences (17) and instead found differences in DNA damage response (17) or oxidative stress response (18).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous EOCRC transcriptomic studies examine differences between EOCRC and LOCRC tumor samples (19,(21)(22)(23), leaving it unclear whether results are important for cancer progression or artifacts of aging tissues. Other studies may have matched control samples but do not control for patient characteristics between EOCRCs and LOCRCs (17), allowing for differences between patient populations, such as stage, gender, tumor location, and histology, to drive EOCRC versus LOCRC differences (13). The variety of genes and gene signatures identified in previous studies may be reflective of different study populations and designs, highlighting the need for a well-controlled study of the EOCRC transcriptome.…”
Section: Introductionmentioning
confidence: 99%